Analisis Peran Dan Strategi Pemerintah Daerah Dalam Mencegah Penyalagunaan Narkotika Di Kalangan Remaja - Hery Setyawan (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2023)
The drug problem in Indonesia is still something that is urgent and complex. In the last decade this problem has become widespread. Evidenced by the significant increase in the number of drug abusers or addicts, along with the increasing disclosure of drug crime cases, the pattern of which is increasingly diverse and the syndicate network is getting more massive. The impact of drug abuse does not only threaten the survival and future of those who abuse it, but also the future of the nation and state, regardless of social, economic strata, age or level of education. Until now the level of drug trafficking has penetrated at various levels, not only in urban areas but has touched rural communities.